2020
DOI: 10.1016/j.epsc.2020.101641
|View full text |Cite
|
Sign up to set email alerts
|

Meckel's diverticulum perforation in a newborn positive to Sars-Cov-2

Abstract: The health emergency linked to the Sars-Cov-2 infection represented an absolutely new problem for all health professionals. In particular, the information regarding the spread of the virus in the pediatric field and its manifestations are still incomplete. In this paper we present a case of neonatal infection which, as far as we know, represents one of the few published cases and which occurred in a patient who came to our attention for acute abdomen from intestinal perforation. The perforation was caused by M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…[7][8][9][10][11] However, most authors suspect that angiotensinconverting enzyme 2 (ACE-2), the primary cellular receptor for SARS-CoV-2, is involved since ACE-2 is highly expressed in the intestinal tract. [1][2][3][4][5][6][7][8]12,13 Consistent with this patient, several reports have documented neutrophilia and increased lymphocytes in COVID-19 patients. [14][15][16][17] Furthermore, autopsies of COVID-19 patients show neutrophil infiltration in pulmonary capillaries and alveolar spaces.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…[7][8][9][10][11] However, most authors suspect that angiotensinconverting enzyme 2 (ACE-2), the primary cellular receptor for SARS-CoV-2, is involved since ACE-2 is highly expressed in the intestinal tract. [1][2][3][4][5][6][7][8]12,13 Consistent with this patient, several reports have documented neutrophilia and increased lymphocytes in COVID-19 patients. [14][15][16][17] Furthermore, autopsies of COVID-19 patients show neutrophil infiltration in pulmonary capillaries and alveolar spaces.…”
Section: Discussionsupporting
confidence: 86%
“…The possibility that COVID-19 infection causes or contributes to development of gastrointestinal perforations has been raised by several case reports affecting all age groups. [2][3][4][5][6][7][8][9] The most common causes proposed for COVID-19 gastric perforations include high-dose steroids, tocilizumab (an interleukin-6 inhibitor), stress-related mucosal damage, and small vessel thrombosis and nonocclusive mesenteric ischemia. [7][8][9][10][11] However, most authors suspect that angiotensinconverting enzyme 2 (ACE-2), the primary cellular receptor for SARS-CoV-2, is involved since ACE-2 is highly expressed in the intestinal tract.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 King Faisal Specialist Hospital & Research Center, Jeddah 21499, Saudi Arabia. 4 Children's Hospital, Lahore, Pakistan. 5 Center for Colorectal and Pelvic Reconstruction, Nationwide Children's, Ohio, Columbus, USA.…”
Section: Abbreviationmentioning
confidence: 99%
“…Although neonates may show more severe illness manifestations [ 4 ], it is rarely reported that infected neonates with COVID-19 present with intestinal perforation (IP) [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%